A decade of labour market reforms in the EU: Insights from the LABREF database - Alessandro Turrini; Gabor Koltay; Fabiana Pierini; Clarisse Goffard; Aron Kiss (IZA Journal of Labor Policy, 2015)
This paper analyses the main features and determinants of labour market reforms in the EU over the period of 2000 - 2011 using the European Commission LABREF database. The data suggests that the timing, focus, and geographical distribution of reforms reflect the interplay between economic shocks and existing institutions. The 2008 crisis was followed by increased policy activity in most policy domains in a large number of EU countries, initially to cushion the impact of the crisis on employment and incomes, subsequently to improve the adjustment capacity of labour markets. Regression analysis indicates that reform activism is stronger in countries with lower GDP per capita and long-standing EU membership, under critical economic and labour market conditions, and where political costs are low. The direction of reforms is affected by economic and labour market conditions, available fiscal space, and by initial policy settings.
Keywords: J20; J38; J48; J58; J68; 330; Labour market; Labour market reform; Unemployment; Financial crisis; European Union